2016
DOI: 10.1038/ijo.2016.147
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a first-degree family history of diabetes to increased serum adipocyte fatty acid binding protein levels independent of body fat content and distribution

Abstract: Background/Objectives:First-degree relatives of patients with diabetes bear an increased risk of diabetes, overweight/obesity and cardiovascular disease. Accumulating evidence indicates that circulating concentrations of adipokines are altered in individuals with a first-degree family history of diabetes (FHD), but the adipokine adipocyte fatty acid binding protein (A-FABP) has been rarely studied in this population. The present study explored the association between a first-degree FHD and serum A-FABP levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
1
8
0
2
Order By: Relevance
“…In addition, our previous studies have reported a significantly positive correlation between serum A‐FABP levels and body fat parameters, such as BMI, W and HOMA‐IR, in 2108 non‐diabetic individuals . The relationship remained unchanged even when we further eliminated the influence of hyperglycaemia . The aforementioned studies suggested that serum A‐FABP levels had a close association with IR.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In addition, our previous studies have reported a significantly positive correlation between serum A‐FABP levels and body fat parameters, such as BMI, W and HOMA‐IR, in 2108 non‐diabetic individuals . The relationship remained unchanged even when we further eliminated the influence of hyperglycaemia . The aforementioned studies suggested that serum A‐FABP levels had a close association with IR.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, basic studies have confirmed that A‐FABP has an effect on inflammatory responses and glycolipid metabolism and plays a key role in obesity, IR and dyslipidaemia . In clinical studies, serum A‐FABP levels were found to contribute to metabolic disorders such as IR, obesity and cardiovascular disease . We have previously observed a significantly positive correlation among serum A‐FABP levels, body fat parameters and IR .…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Due to type 2 diabetes being an inherited disease, we considered relevant to understand if the increased risk of developing type 2 diabetes in individuals with a rst-degree family history of diabetes (15), would further play a role in modifying the association of soft drinks and the risk of type 2 diabetes. We hypothesized that having a family history of diabetes could have a synergistic effect with soft drinks that could increase the type 2 diabetes risk.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, genetic defects in FDR can regulate the transcription of cytokine genes, resulting in abnormalities of the secretion and metabolism of cytokines [4]. Our previous studies have found that the levels of adipokines in FDR are significantly increased, possibly because of impaired insulin function [5].…”
Section: Introductionmentioning
confidence: 99%